The influence of career stage on police officer work behavior - Johnson, Richard R. (Criminal justice and behavior, 2016)
Career stage theory suggested that workers progress through career stages, each marked by unique work attitudes. Little evidence exists, however, about the influence career stages have on the work activities of criminal justice agents. Using a sample of 401 police officers from 23 individual police departments, the present study examined the influence of employee career stage on three measures of work productivity, and the constructs of expectancy motivation theory. The results revealed curvilinear declines in productivity with progression through the career stages. The predictive values of opportunity, ability, and instrumentality on work activities varied with career stage and type of work output. Only performance-reward expectancy retained predictive value across all career stages and outputs. The findings emphasize the importance of intrinsic and informal extrinsic rewards for the management of experienced criminal justice agents.